The role of work engagement as a mediator in the relationship between forgiveness at work and job satisfaction - Friska Utami Saraswati Sembiring; Rahmi Lubis; Patisina Patisina (Jurnal Konseling dan Pendidikan, 2025)
Understanding the psychological mechanisms that enhance job satisfaction remains a critical issue, particularly in organizational contexts characterized by high interpersonal demands. Forgiveness at work has been increasingly recognized as a positive psychological resource that may foster healthier work relationships; however, its underlying mechanism in shaping job satisfaction remains underexplored. This study aims to examine the mediating role of work engagement in the relationship between forgiveness at work and job satisfaction. Using a quantitative approach, data were collected from 456 permanent employees of a private organization in Indonesia and analyzed using Structural Equation Modeling (SEM) with SmartPLS. The findings indicate that forgiveness at work has a significant indirect effect on job satisfaction through work engagement, demonstrating a meaningful mediation relationship. These results suggest that forgiveness contributes to job satisfaction primarily by strengthening employees’ emotional and cognitive attachment to their work. The study provides theoretical insight by clarifying the psychological pathway linking forgiveness and job satisfaction, and offers practical implications for organizations seeking to enhance employee well-being through relational and engagement-based interventions.